Penguatan Literasi Digital Siswa SMAN 23 Makassar melalui Workshop Penggunaan Pembelajaran Digital - Asri Nur Aina; Nur Fadhilah Umar; Zulfikri; Muhammad Ansarullah S. Tabbu (IKRA-ITH ABDIMAS, 2025)
The rapid development of digital technology requires students to possess adequate digital literacy skills to support learning processes that are increasingly integrated with digital media. However, preliminary observations at SMAN 23 Makassar indicate that students’ abilities in utilizing learning applications, managing information, and comprehending digital content remain varied, thus necessitating a more targeted intervention. This community service program aims to enhance students’ digital literacy through a workshop on the use of digital learning applications, specifically Powtoon and Prezi. The implementation method adopts an interactive workshop approach consisting of socialization, technical training, technology application in learning activities, as well as mentoring and evaluation. During the socialization phase, students were provided with an understanding of the urgency of digital literacy in addressing contemporary learning challenges. The training phase offered opportunities for students to become familiar with the basic features of the applications and to develop technical skills through hands-on practice. Implementation results demonstrate an improvement in students’ abilities to create visual summaries, present conceptual understanding, and manage digital content more systematically. Subsequent mentoring further revealed that students became increasingly motivated, adaptive, and confident in utilizing technology as part of their learning strategies. These findings align with previous studies asserting that digital literacy training can enhance students’ critical thinking, creativity, and active participation in digital learning environments. Thus, the workshop proved effective in strengthening the technical, cognitive, and motivational dimensions of students’ digital literacy, contributing significantly to their preparedness in navigating the dynamics of learning in the digital era.